Sovereign Spreads and the Effects of Fiscal Austerity - Diego Anzoategui (Rutgers University, Department of Economics, 2020)
I analyze the impact of austerity on sovereign spreads. To do so I propose a model with strategic sovereign default and nominal rigidities where the government follows fiscal rules, which are estimated from data. I first analyze the theoretical implications of the model and find that austerity can be self-defeating only when austerity packages are persistent and the economy is expected to be in a recession with high fiscal multipliers. I then calibrate the model using data from Spain and estimate the size and impact of fiscal policy shocks associated with austerity policies. I use the model to predict what would have happened to spreads and economic activity if Spain had continued to follow the pre-2010 fiscal rule instead of switching to the austerity track. I find that, relative to the counter-factual, austerity decreased sovereign spreads and debt-to-GDP ratios even when fiscal multipliers where higher than one during 2010-2013. Overall, the results indicate that the likelihood of facing self-fulfilling austerity episodes depends on the magnitude of fiscal multipliers but is generally low.
Keywords: F34; E62; 330; Austerity; Sovereign Default